2014
DOI: 10.1111/soc4.12132
|View full text |Cite
|
Sign up to set email alerts
|

Physical Attractiveness and Social Status

Abstract: In this article, we outline the evidence regarding the status effects of physical attractiveness, paying particular attention to outcomes in the areas of jobs, crime, performance evaluations, power, health perceptions, and exchange. The framework of status characteristics theory is used to guide our explication. The role of attractiveness in marketing is also discussed. While the literature generally supports the idea that attractiveness is good for people, we also consider evidence that beauty can be detrimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…Facial skin aging is of global concern as it is linked to beauty, social acceptance, and status . It was identified as one of the most important challenges in global skin health by the International League of Dermatological Societies .…”
Section: Introductionmentioning
confidence: 99%
“…Facial skin aging is of global concern as it is linked to beauty, social acceptance, and status . It was identified as one of the most important challenges in global skin health by the International League of Dermatological Societies .…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies stressed traditional sex roles in the perception of beauty [ 2 , 3 ], which means that women are assumed to be more affected by their looks than men. However, we did not find significant gender differences in the association between reported appearance discrimination and poor self-rated health among emerging adults in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Sociological literature has accumulated that physical attractiveness is socially constructed, and in general it is positively associated with quality of social experiences [ 1 – 3 ]. Empirical studies show that persons who are not physically attractive are disadvantaged in society, particularly in labor, education, and marriage markets [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Females feel pressurized to appear attractive purposely for getting the benefits in their education, career and social life (Verbickaite 2017). Frevert & Walker (2014) found that attractive people are perceived to be healthier, less likely to commit crime, more likely to win in elections, have better relationships, more powerful, look more intelligent and even have some benefits in employment since ones personality is influenced by the perception of ones looks.…”
Section: Introductionmentioning
confidence: 99%